The Effect of STEM-based History Podcast Media on Literacy in Digital Era through ICT Courses for History Education Students - Maryuni, Yuni; Ribawati, Eko; Prasadana, Muhammad Anggie Farizqi; Nurhasanah, Ana; Wibowo, Tubagus Umar Syarif Hadi; Nashar, Nashar; Fauzan, Rikza; Putra, Arif Permana; Sari, Indah Juwita (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Only now has learning by mainstreaming authentic educational skills yet to exist. By following mechanical advances, learning media are increasingly diverse, including web transcription media that can be used as learning media in the classroom. Authentic digital recordings with STEM awareness so that learning can begin in a multi-teacher manner to prepare students for demonstrable proficiency abilities. This study aims to determine the effect of using STEM-combined verification digital broadcast media on the verification abilities of students in ICT courses. The strategy used in this exploration is a semi-exploratory technique using a quasi-experimental nonequivalent control group design with two classes: a control class and an experimental class. Based on the analysis of the information obtained, the test value of the habit test (pretest-posttest) obtained an x2table value of 11.07 with a significance level of 0.05. The experimental class pretest x2count value was 10.92, the control class pretest x2count was 0.87, and the experimental class posttest x2count value was -18.81. The control class posttest x2count value was 4.22, the pretest-posttest data homogeneity test results obtained a Ftable 1.73 with a significance level of 0.05, the pretest Fcount value was 1.31, and the posttest was 1.57. The posttest data showed that the tcount value of 3.32 was not the same as the ttable value of 1.67, so Ho was rejected. H1 was accepted. STEM-based historical podcast media influences historical literacy skills in ICT History Education students.